Exploring the Synthesis and Bioactive Properties of Coumarin-1,2,3-Triazole Conjugates - de A. Borges, Amanda; P. V. de Carvalho, Yuri; V. T. Martins, Cristal; G. R. da Cruz, Analice; Evangelista, Edson; de C. da Silva, Fernando; da S. M. Forezi, Luana (Journal of the Brazilian Chemical Society, 2025)
A survey of the literature reveals that both coumarin and the 1,2,3-triazole nucleus have important and well-recognized biological and pharmaceutical activities. Furthermore, these fused scaffolds have demonstrated biological significance, making the design and development of coumarin-1,2,3-triazole hybrids a topic of great interest in the field of synthetic organic chemistry and medicinal chemistry. The wide-ranging applications of coumarin and triazole have stimulated interest among researchers to develop various methodologies for synthesizing new molecules incorporating these moieties. Consequently, numerous research and review articles have been published on the subject. In this review, we present some research conducted over the past five years on bioactive coumarin-1,2,3-triazole hybrids, with an emphasis on the synthesis of these compounds and their biological applications in the treatment of infectious diseases, cancer, and Alzheimer’s disease.